Exercise as an Adjuvant Therapy for Hematopoietic Stem Cell Mobilization - Russell Emmons; Grace M. Niemiro; Michael De Lisio (Stem Cells International)
Hematopoietic stem cell transplant (HSCT) using mobilized peripheral blood hematopoietic stem cells (HSPCs) is the only curative strategy for many patients suffering from hematological malignancies. HSPC collection protocols rely on pharmacological agents to mobilize HSPCs to peripheral blood. Limitations including variable donor responses and long dosing protocols merit further investigations into adjuvant therapies to enhance the efficiency of HSPCs collection. Exercise, a safe and feasible intervention in patients undergoing HSCT, has been previously shown to robustly stimulate HSPC mobilization from the bone marrow. Exercise-induced HSPC mobilization is transient limiting its current clinical potential. Thus, a deeper investigation of the mechanisms responsible for exercise-induced HSPC mobilization and the factors responsible for removal of HSPCs from circulation following exercise is warranted. The present review will describe current research on exercise and HSPC mobilization, outline the potential mechanisms responsible for exercise-induced HSPC mobilization, and highlight potential sites for HSPC homing following exercise. We also outline current barriers to the implementation of exercise as an adjuvant therapy for HSPC mobilization and suggest potential strategies to overcome these barriers.